Analisis Faktor-Faktor Resiko Infeksi Cacing Pita pada Ayam Ras Petelur Komersial di Bogor - Budi Retnani, Elok; Satrija, Fadjar; Kesumawati Hadi, Upik; Harsoyo Sigit, Singgih (Jurnal Veteriner, 2009)
A cross-sectional study was conducted in Bogor Region, West Java for two months from June to July2006. The aim of this research was to identify the risk factors of cestode infection in commercial cagedlayer chickens. A total of 202 chicken samples were collected from ten commercial caged layer chickenfarms. The risk factors assumption included host factors, farm environment and management characteristic.Logistic regression model showed that cestode infection risk association (P<0,01) to host age, (P<0,05) todry climate condition and open house farm management characteristic. This suggests that >50 monthshave higher risk (OR=5.6) than <20 months host age, dry climate condition have higher risk (OR=3.75)than wet, and open house farm management have higher risk (OR=27.24) than close house on the cestodesinfection.
Keywords: Cestodes, caged layer chickens, infection risk factors, Oods-Ratio, Bogor